Phytopharmacological overview of Tribulus terrestris - Chhatre, Saurabh; Nesari, Tanuja; Somani, Gauresh; Kanchan, Divya; Sathaye, Sadhana (Pharmacognosy Reviews)
Tribulus terrestris (family Zygophyllaceae), commonly known as Gokshur or Gokharu or puncture vine, has been used for a long time in both the Indian and Chinese systems of medicine for treatment of various kinds of diseases. Its various parts contain a variety of chemical constituents which are medicinally important, such as flavonoids, flavonol glycosides, steroidal saponins, and alkaloids. It has diuretic, aphrodisiac, antiurolithic, immunomodulatory, antidiabetic, absorption enhancing, hypolipidemic, cardiotonic, central nervous system, hepatoprotective, anti‑inflammatory, analgesic, antispasmodic, anticancer, antibacterial, anthelmintic, larvicidal, and anticariogenic activities. For the last few decades or so, extensive research work has been done to prove its biological activities and the pharmacology of its extracts. The aim of this review is to create a database for further investigations of the discovered phytochemical and pharmacological properties of this plant to promote research. This will help in confirmation of its traditional use along with its value‑added utility, eventually leading to higher revenues from the plant.
Keywords: Pharmacology; saponin; tribulus terrestris